A Simple Culture Method Enhances the Recovery of Culturable Actinobacteria From Coastal Sediments - Huang, Zhaobin; Mo, Shiqing; Yan, Lifei; Wei, Xiaomei; Huang, Yuanyuan; Zhang, Lizhen; Zhang, Shuhui; Liu, Jianzong; Xiao, Qingqing; Lin, Hong; Guo, Yu (Frontiers in Microbiology, 2021)
Molecular methods revealed that the majority of microbes in natural environments remain uncultivated. To fully understand the physiological and metabolic characteristics of microbes, however, culturing is still critical for microbial studies. Here, we used bacterial community analysis and four culture media, traditional marine broth 2216 (MB), water extracted matter (WEM), methanol extracted matter (MEM), and starch casein agar (SCA), to investigate the diversity of cultivated bacteria in coastal sediments. A total of 1,036 isolates were obtained in pure culture, and they were classified into 5 groups, Alphaproteobacteria (52.51%), Gammaproteobacteria (23.26%), Actinobacteria (13.32%), Firmicutes and Bacteroidetes. Compared to other three media, WEM recovered a high diversity of actinobacteria (42 of 63 genotypes), with Micromonospora and Streptomyces as the most cultivated genera. Amplicon sequencing of the bacterial 16S rRNA gene V3-V4 fragment revealed eight dominant groups, Alphaproteobacteria (12.81%), Gammaproteobacteria (20.07%), Deltaproteobacteria (12.95%), Chloroflexi (13.09%), Bacteroidetes (8.28%), Actinobacteria (7.34%), Cyanobacteria (6.20%) and Acidobacteria (5.71%). The dominant members affiliated to Actinobacteria belonged to ‘Candidatus Actinomarinales’, ‘Ca. Microtrichales’, and Nitriliruptorales. The cultivated actinobacteria accounted for a small proportion (<5%) compared to the actinobacterial community, which supported that the majority of actinobacteria are still waiting for cultivation. Our study concluded that WEM could be a useful and simple culture medium that enhanced the recovery of culturable actinobacteria from coastal sediments.